The Urgency of Protecting Children from Physical and Sexual Violence: A Human Rights Perspective - Bone, Sholihin (Constitutional Law Review, 2024)
This research aims to analyze the urgency of protecting children from acts of physical and sexual violence in Balikpapan City from a human rights perspective. Violence against children not only damages the victims psychologically and physically but also threatens their future. This research uses empirical juridical methods with a statutory and comparative approach. Data was collected through interviews with stakeholders and analysis of legislation and related literature. The research results show that although existing regulations have run child protection efforts in Balikpapan City, there are still various obstacles, such as low public awareness, limited facilities and infrastructure, as well as challenges in dealing with victims with disabilities. From a human rights perspective, child protection is a state obligation that includes respecting, protecting, and fulfilling children's rights. This research recommends increasing public outreach and education, strengthening digital protection policies, collaborating with religious leaders, and improving assistance services and infrastructure to ensure more effective protection. With integrated and sustainable efforts, children's rights in Balikpapan City are hoped to be better protected, allowing them to grow and develop in a safe and supportive environment